First Neotropical species of genus Azana (Diptera: Mycetophilidae: Sciophilinae) - de Souza Amorim, Dalton; Oliveira, Sarah Siqueira; Balbi, Maria Isabel P. A. (Zootaxa, 2008)
The Fourth Edition of the International Code of Zoological Nomenclature (ICZN 1999) stated specific rules for the validity of species name associated, one of them the indication of the depository of the primary type. Particularly, Article 16.4 states that the description “(...) must be accompanied in the original publication (...) by a statement of intent that they will be (or are) deposited in a collection and a statement indicating the name and location of that collection.” Deposition of types is also dealt with in Articles 72.10, 73C, 74D, 75.3.7.